Kedai Kopi Sebelas / Nur Atiqah Shariffuddin … [et al.] - SHARIFFUDDIN, NUR ATIQAH; MOHAMAD RUSOP, NUR AUNI; MOHAMAD RUSOP, NUR INANI; MD KHAIRI, NURUL FARHANA (2018)
Kedai Kopi Sebelas is a family-owned restaurant located at Section 11, Shah Alam. It serves various kind of coffees and drinks. It also serves local food such as Nasi Lemak and Nasi Gulai. This Kedai Kopi Sebelas at Section 11 is the first branch and only started the operation for eight months.